Evaluati on de l‟activité des param ètres biochimiques chez l es femmes atteintes d‟hypothyroïdie - BELMILOUD, IMEN; AMRANI, ROKIA (My University, 2020)
Currently, thyroid disease is one of the most common hormonal disorders seen in our society. Women are the most common being with hypothyriodism. Our work consists of carrying out a study on thyroid pathology, hypothyroidism and the prevalence of thyroid disorders in subjects who have an indication of a thyroid workup, we prepose to study the impact of replacement therapy on metabolic disorders in women. A case / control study was carried out 34 women ,including 17 hypothyroid women treatment with evothyroxine and 17 control women, and the second study is carried out on a population of 42 women (healthy and with hypothyroidism) to determine the effect of biochemical parameters on body metabolism in women with hypothyroidism. To do this, we carried out a comparative study of the plasma levels of different biochemical parameters (creatinine, cholesterol, triglycerides, urea and plasma proteins) in people with hypothyroidism under treatment or not with healthy controls. The results show that a dysfunction in the thyroid has direct repercussions on the content of creatinine, urea, in addition to lipids and total proteins... In conclusion, this modification is important and can alter the functioning of the body metabolism of patients which can subsequently induce other much more serious complications.
Keywords: hypothyroidism; metabolism; treatment substitute